K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

13 tháng 9 2018

=(3x mũ 2 + 3x+2-3x mũ 2 -3x +2).(3x mũ 2 + 3x +2 +3x mũ 2 +3x -2)=4.(6x mũ 2+6x)

a: \(=\dfrac{2x\left(3x^2+2\right)+3x^2+2}{3x^2+2}=2x+1\)

b: 

Sửa đề: 6x^4-4x^3+3x-2/3x-2

\(=\dfrac{6x^4-4x^3+3x-2}{3x-2}\)

\(=\dfrac{2x^3\left(3x-2\right)+3x-2}{3x-2}=2x^3+1\)

18 tháng 12 2021

Bài 1:

\(a,=6x^2+6x\\ b,=15x^3-10x^2+5x\\ c,=6x^3+12x^2\\ d,=15x^4+20x^3-5x^2\\ e,=2x^2+3x-2x-3=2x^2+x-3\\ f,=3x^2-5x+6x-10=3x^2+x-10\)

Bài 2:

\(a,\Leftrightarrow3x^2+3x-3x^2=6\\ \Leftrightarrow3x=6\Leftrightarrow x=2\\ b,\Leftrightarrow6x^2+3x-6x^2+9x-2x-3=10\\ \Leftrightarrow10x=13\Leftrightarrow x=\dfrac{13}{10}\)

19 tháng 10 2021

D

a: Ta có: \(\left(x^2+2\right)\left(x-4\right)-\left(x+2\right)^3=-16\)

\(\Leftrightarrow x^3-4x^2+2x-8-x^3-6x^2-12x-8=-16\)

\(\Leftrightarrow-10x^2-10x=0\)

\(\Leftrightarrow-10x\left(x+1\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=-1\end{matrix}\right.\)

c: Ta có: \(x^3+3x^2+3x+28=0\)

\(\Leftrightarrow\left(x+1\right)^3=-27\)

\(\Leftrightarrow x+1=-3\)

hay x=-4

17 tháng 9 2021

\(1,\\ a,=3x^3-2x^2+5x\\ b,=2x^3y^2+\dfrac{2}{9}x^4y^2-\dfrac{1}{3}x^2y^3\\ c,=x^2-2x+6x-12=x^2+4x-12\\ 2,\\ a,\Rightarrow6x-9+4-2x=-3\\ \Rightarrow4x=2\Rightarrow x=\dfrac{1}{2}\\ b,\Rightarrow5x-2x^2+2x^2-2x=13\\ \Rightarrow3x=13\Rightarrow x=\dfrac{13}{3}\\ c,\Rightarrow5x^2-5x-5x^2+7x-10x+14=6\\ \Rightarrow-8x=-8\Rightarrow x=1\\ d,\Rightarrow6x^2+9x-6x^2+4x-15x+10=8\\ \Rightarrow-2x=-2\Rightarrow x=1\)

 

17 tháng 9 2021

\(3,\\ A=2x^2+x-x^3-2x^2+x^3-x+3=3\\ B=6x^2-10x+33x-55-6x^2-14x-9x-21=-76\)

3 tháng 3 2022

\(a,3x^2+5x+2=0\\ \Leftrightarrow\left(3x^2+3x\right)+\left(2x+2\right)=0\\ \Leftrightarrow3x\left(x+1\right)+2\left(x+1\right)=0\\ \Leftrightarrow\left(3x+2\right)\left(x+1\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{2}{3}\\x=-1\end{matrix}\right.\)

b, ĐKXĐL\(x\ne\pm\dfrac{2}{3}\)

\(\dfrac{3x+2}{3x-2}-\dfrac{6}{2+3x}=\dfrac{9x^2}{9x^2-4}\\ \Leftrightarrow\dfrac{\left(3x+2\right)^2}{\left(3x+2\right)\left(3x-2\right)}-\dfrac{6\left(3x-2\right)}{\left(3x+2\right)\left(3x-2\right)}-\dfrac{9x^2}{\left(3x+2\right)\left(3x-2\right)}=0\\ \Leftrightarrow\dfrac{9x^2+12x+4-18x+12-9x^2}{\left(3x+2\right)\left(3x-2\right)}=0\\ \Leftrightarrow-6x+16=0\\ \Leftrightarrow x=\dfrac{8}{3}\left(tm\right)\)

HQ
Hà Quang Minh
Giáo viên
19 tháng 9 2023

a) 2x(x+3) – 3x2(x+2) + x(3x2 + 4x – 6)

= (2x . x + 2x . 3) – (3x2 . x + 3x2 . 2) + (x . 3x2 + x . 4x – x . 6)

= 2x2 + 6x – (3x3 + 6x2) + (3x3 + 4x2 - 6x)

= 2x2 + 6x – 3x3 – 6x2 + 3x3 + 4x2 - 6x

= (– 3x3 + 3x3 ) + (2x2  - 6x2 + 4x2 ) + (6x – 6x)

= 0 + 0 + 0

= 0

b) 3x(2x2 – x) – 2x2(3x+1) + 5(x2 – 1)

= [3x . 2x2 + 3x . (-x)] – (2x2 . 3x + 2x2 . 1) + [5x2 + 5 . (-1)]

= 6x3 – 3x2 – (6x3 +2x2) + 5x2 – 5

= 6x3 – 3x2 – 6x3 - 2x2 + 5x2 – 5

= (6x3 – 6x3 ) + (-3x2 – 2x2 + 5x2) – 5

= 0 + 0 – 5

= - 5

a: =>3x+10-2x=0

hay x=-10

c: \(\Leftrightarrow3x^2-3x^2+6x=36\)

=>6x=36

hay x=6

1) Ta có: \(2x\left(x-3\right)+5\left(x-3\right)=0\)

\(\Leftrightarrow\left(x-3\right)\left(2x+5\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=-\dfrac{5}{2}\end{matrix}\right.\)

2) Ta có: \(\left(x^2-4\right)-\left(x-2\right)\left(3-2x\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(x+2\right)+\left(x-2\right)\left(2x-3\right)=0\)

\(\Leftrightarrow\left(x-2\right)\left(3x-1\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=2\\x=\dfrac{1}{3}\end{matrix}\right.\)

3) Ta có: \(\left(2x-1\right)^2-\left(2x+5\right)^2=11\)

\(\Leftrightarrow4x^2-4x-1-4x^2-20x-25=11\)

\(\Leftrightarrow-24x=11+1+25=37\)

hay \(x=-\dfrac{37}{24}\)

 

5) Ta có: \(3x^2-5x-8=0\)

\(\Leftrightarrow3x^2+3x-8x-8=0\)

\(\Leftrightarrow3x\left(x+1\right)-8\left(x+1\right)=0\)

\(\Leftrightarrow\left(x+1\right)\left(3x-8\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=\dfrac{8}{3}\end{matrix}\right.\)

8) Ta có: \(\left|x-5\right|=3\)

\(\Leftrightarrow\left[{}\begin{matrix}x-5=3\\x-5=-3\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=8\\x=2\end{matrix}\right.\)

10) Ta có: \(\left|2x+1\right|=\left|x-1\right|\)

\(\Leftrightarrow\left[{}\begin{matrix}2x+1=x-1\\2x+1=1-x\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}2x-x=-1-1\\2x+x=1-1\end{matrix}\right.\)

\(\Leftrightarrow\left[{}\begin{matrix}x=-2\\x=0\end{matrix}\right.\)

`1,`

`a,`

`3x(x^2-3x+2)`

`= 3x*x^2+3x*(-3x)+3x*2`

`= 3x^3-9x^2+6x`

`b,`

`(3x^2+x) \div 3x`

`= 3x^2 \div 3x + x \div 3x`

`= x + 1/3`

11 tháng 5 2023

Or~~~~~~ Iu iu<3